2011
DOI: 10.1080/14786411003774312
|View full text |Cite|
|
Sign up to set email alerts
|

Volatile oil constituents and antibacterial activity of different parts ofFalcaria vulgarisBernh. growing wild in two localities from Iran

Abstract: The chemical composition of essential oils obtained by hydrodistillation from the flower, leaf and stem of Falcaria vulgaris Bernh., which is endemic to Iran, were analysed by GC and GC/MS (samples were from two different localities: A from Ardabil and B from Khalkhal). α-Pinene was the major constituent in all the three oils (flower, leaf and stem) from sample A (43.8%, 33.0% and 50.9%, respectively). The oil of F. vulgaris flower was characterised by a higher amount of β-caryophyllene (25.2%) and 1,8-cineole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Thus, compounds with antioxidant activity can ameliorate these changes and prevent the progression of nephropathy [52]. F. vulgaris as a medicinal plant rich in antiinflammatory and antioxidant compounds such as spathulenol, carvacrol, alpha-pinene and limonene, and it has strong antiinflammatory and antioxidant properties [20,53,54]. Previous studies have indicated that ethnomedicinal plants rich in antiinflammatory and antioxidant compounds decrease weight, volumes and lengths of kidney and its subcomponents in STZ-induced nephrotoxicity in mice [55,56].…”
Section: Nephroprotective Effect Of F Vulgarismentioning
confidence: 99%
“…Thus, compounds with antioxidant activity can ameliorate these changes and prevent the progression of nephropathy [52]. F. vulgaris as a medicinal plant rich in antiinflammatory and antioxidant compounds such as spathulenol, carvacrol, alpha-pinene and limonene, and it has strong antiinflammatory and antioxidant properties [20,53,54]. Previous studies have indicated that ethnomedicinal plants rich in antiinflammatory and antioxidant compounds decrease weight, volumes and lengths of kidney and its subcomponents in STZ-induced nephrotoxicity in mice [55,56].…”
Section: Nephroprotective Effect Of F Vulgarismentioning
confidence: 99%
“…Phytochemical analysis showed that the major components of F. vulgarisʼs volatile oil belong to sesqui-and mono-terpene groups of chemicals. 17,18 In I. tataricum Pallas (Ixioliriaceae), the dominant components were found to be 2-phenylethyl phenylacetate, β-selinene, bicyclovetivenol, thymol, and chalcone. 19 A broad spectrum of physiological and medicinal properties were attributed to the species of this family including the following: anti-inflammatory (Liu et al, 2015), acetylcholinesterase inhibitory, 20 immunostimulatory, and DNAbinding activities.…”
Section: Introductionmentioning
confidence: 99%
“…is a member of Apiaceae family with distinct biological antiaging activities among others, such as antioxidant, skin healing, antidiabetic, hepato‐ and hemato‐protective properties and many other pharmacological effects. Phytochemical analysis showed that the major components of F. vulgaris 's volatile oil belong to sesqui‐ and mono‐terpene groups of chemicals …”
Section: Introductionmentioning
confidence: 99%
“…Despite the use of preservatives to control microorganisms that cause food spoilage and infection, food safety is an important challenge in the industry. Currently, the use of natural preservatives is a healthy and effective alternative to chemicals (Shafaghat, 2011). Evaluation of antibacterial activity is necessary to determine the activity of edible lm against bacterial pathogens for different applications.…”
Section: Antimicrobial Assaymentioning
confidence: 99%